(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Role of Partnership Structuringand Negotiations are determined as the partnership agreement(and the project itself) is structured and negotiated. The nature and structureof the PPP agreement itself is particularly important. Morlok (1993) describeseight common-sense “guidelines for choosing a partner and making therelationship work.” These include careful selection of a committed partner,honesty and clarity about goals and objectives, and specific language detailingroles, responsibilities, and decision-making authority. Obviously, theselection of a (or which) private partner is vitally important. Wheneverpossible, some type of competitive-selection process should be utilized, bothfor appearance reasons and for obtaining the most aggressive or committedprivate partner. (Stainback, 2000; Sagalyn, 1996)